Advertisement Remove all ads

Solve for x : 2/(x+1)+3/(2(x-2))=23/(5x), x!=0, -1 ,2 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Solve for x :

`2/(x+1)+3/(2(x-2))=23/(5x), x!=0,-1,2`

Advertisement Remove all ads

Solution

`2/(x+1)+3/(2(x-2))=23/(5x)`

`=>(4(x-2)+3(x+1))/(2(x+1)(x-2))=23/(5x)`

`=>(7x-5)/(2(x^2-x-2))=23/(5x)`

 5x(7x5)=46(x2x2)

11x221x92=0

11x244x+23x92=0

11x(x4)+23(x4)=0

(11x+23)(x4)=0

`=>x = -23/11,4`

Concept: Solutions of Quadratic Equations by Factorization
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×